Gambaran Pola Pemberian Makanan Pendamping ASI (MP-ASI) dan Status Gizi Balita Usia 6-24 Bulan di Wilayah Kerja Puskesmas Kioko Kelurahan Bonegunu Kabupaten Buton Utara 2023 - Yulan Sari; Wa Ode Salma; Syefira Salsabila (KOLONI, 2023)
One of the health problems currently existing in Indonesia is malnutrition. A factor that can influence a person's nutrition is diet. Diet is closely related to the type, amount and frequency of food consumed every day. Fulfillment of good food for children will affect the nutritional status of children. The aim of this research is to dig deeper into the description of complementary breastfeeding and the nutritional status of toddlers at the Kioko Community Health Center, Bonegunu Village, North Buton Regency. This research uses a qualitative approach method. Determining the sample in this research used a purposive sampling technique, namely a technique for determining informants based on certain criteria determined by the researcher himself. The research results show that the factors causing poor nutritional status are frequency of eating, mother's knowledge and family economic status.